2014
DOI: 10.1007/s12070-014-0771-x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Allergic Fungal Rhinosinusitis: Ophthalmic and Skull Base Complications

Abstract: To review the clinical features, ophthalmic and skull base complications, radiologic correlates, surgical methods and outcomes in cases of extensive allergic fungal rhinosinusitis (AFRS). The retrospective review was carried out at a tertiary referral center and included 11 patients with extensive AFRS. Inclusion criteria were confirmed cases of AFRS with intracranial extension, gross erosion of the skull base or medial orbital wall and/or ophthalmic complications of AFRS, including visual loss. Acute bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Ashish V, et al has reported sudden visual loss in one of four patients. Patient had complete visual recovery (6/6) due to intravenous steroid administration even before surgical decompression [38]. In our case, patient's visual loss improved post operatively along with use of oral steroids as well.…”
Section: Afrs With Intraorbital Extensionmentioning
confidence: 49%
See 1 more Smart Citation
“…Ashish V, et al has reported sudden visual loss in one of four patients. Patient had complete visual recovery (6/6) due to intravenous steroid administration even before surgical decompression [38]. In our case, patient's visual loss improved post operatively along with use of oral steroids as well.…”
Section: Afrs With Intraorbital Extensionmentioning
confidence: 49%
“…The proximity of neurovascular structures to the nasal cavity and sinuses put them at risk of injury, either from the disease process itself or from surgical management. These structures include the internal carotid artery, cranial nerves, cavernous sinus, dura mater and cerebral lobes [38]. The expansion of the disease usually is determined by location of the disease, as well as the path of least resistance.…”
Section: Afrs With Intraorbital Extensionmentioning
confidence: 99%
“…Also the anaerobiosis favours the association with aspergilloma 4 . The spreading mecha-nisms leading to major complications are through continuity, contiguity and haematogenous spreading 5 . There are three possible major complications of RS: endocranial, oculo-orbital and broncho-pulmonary 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for AFRS typically involves surgical and medical management . The most common ophthalmic features of AFRS are proptosis, diplopia and vision loss . Epiphora alone is an atypical presentation …”
mentioning
confidence: 99%
“…1 The most common ophthalmic features of AFRS are proptosis, diplopia and vision loss. 5 Epiphora alone is an atypical presentation. 6 A 33-year-old man presented with complaints of chronic epiphora in both eyes and blurry vision in the left eye.…”
mentioning
confidence: 99%